FINANCIAL AND ECONOMIC EVALUATION OF THE LIVESTOCK FUND OF THE AGRICULTURAL INITIATIVE IN IRAQ FOR THE PERIOD (2009-2018) - Al khazeli, M. H. O.; Al-Badri, B. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The demand for livestock products (dairy, meat, eggs) is characterized by a continuous increase in its basic importance as well as being essential in the prevailing food pattern domestically. The livestock sector suffers from a problem of poor funding and the investor’s inability to compete for several reasons, the most important of which is the high interest on loans granted by institutions. Borrowing, and since the project needs large capital, it will make the investor a loser without any doubt. The demand for livestock products is characterized by a continuous increase in its basic importance and its entry as a major component of the prevailing food pattern locally. With the exception of the governorates of Nineveh and Salah al-Din for the period (2009-2013), it decreased to less than 50% for the period (2014-2018) and the reason is due to the events that occurred in addition to the repeated postponement decisions for all loans within the Federal Budget Law. The rate of late loan collection is low in all governorates for the period studied (2009-2016), as the average did not exceed 62% in 2016, or the lowest average was in 2010 by 4.5%, and the reason for this is that the projects that were lagged in repayment are either that the rates of completion Their operation is low from the beginning, or poorly managed and subject to repeated epidemiological injuries. The research also found that the rates of collection of the livestock fund increased, reaching the highest in 2012 (87.3) with a standard deviation (0.202) and the lowest average in 2018 (43.1) with a standard deviation (0.220) as it shows clearly the progress of the central and southern governorates over the other covered governorates.